(untitled) (Cambridge, 1997)
This book describes recent progress. The book begins with a brief history and outline of developments in thermal system design. Chapters then discuss computer design tools for the power and chemical industries, predicting physical properties with computational tools, "pinch analysis" to improve thermal efficiency, applications of the energy concept, thermoeconomics, and the potential for artificial intelligence and expert systems in the design of thermal systems.
Keywords: Heat engineering,Systems engineering,Engineering design,Kỹ thuật nhiệt,Hệ thống kỹ thuật,Thiết kế kỹ thuật